Supervised pelvic floor muscle exercise is more effective than unsupervised pelvic floor muscle exercise at improving urinary incontinence in prostate cancer patients following radical prostatectomy – a systematic review and meta-analysis. Issue 19 (11th September 2022) - Baumann, Freerk T.; Reimer, Nadine; Gockeln, Theresa; Reike, Alexandra; Hallek, Michael; Ricci, Christian; Zopf, Eva M.; Schmid, Daniela; Taaffe, Dennis; Newton, Robert U.; Galvao, Daniel A.; Leitzmann, Michael
Abstract: Background: Urinary incontinence is one of the most clinically relevant side effects in the treatment of prostate cancer patients. The aim of this systematic review and meta-analysis was to analyze the specific exercise effects of supervised versus unsupervised pelvic floor muscle exercise (PFME) and exercise volume on urinary incontinence status after radical prostatectomy. Methods: A systematic data search was performed for studies published from January 2000 to December 2020 using the following databases: PubMed, Embase, SciSearch, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Database of Abstracts of Reviews and Effects. The review was undertaken according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A random-effects meta-analysis of urinary incontinence remission was performed. The relation between time since surgery and urinary incontinence remission was analyzed using a non-linear dose-response meta-analysis. Results: The meta-analysis included 20 randomized controlled trials involving 2188 men ( n = 1105 in intervention groups; n = 1083 in control groups). PFME versus no PFME had a beneficial effect on urinary incontinence remission at 3 months, 3–6 months, and more than 6 months post-surgery, with risk differences ranging from 12 to 25%. These effects were particularly evident for higher volume, supervised PFME in the first 6 months post-surgery. Additional biofeedback therapy appeared to be beneficial but only during the first 3 months post-surgery. Conclusions: There is good evidence that the supervised PFME causes a decrease in short-term urinary incontinence rates. Unsupervised PFME has similar effects as no PFME in postoperative urinary incontinence. PFME programs should be implemented as an early rehabilitative measure to improve postoperative short-term urinary incontinence in patients with prostate cancer. IMPLICATIONS FOR REHABILITATION: Prostate cancer, surgery, and urinary incontinence The surgical treatment of prostate cancer often leads to urinary incontinence. Pelvic floor training leads to a significant improvement of this situation. Exercise therapy support is very important in this context and is even more effective than unsupported training.